RANTAI PEMASARAN USAHA PRODUK JAHE MERAH (Zingiber officinale var. rubrum) INSTAN “BAJAKAH” UKM CAHAYA SEJAHTERA DI KELURAHAN LANDASAN ULIN UTARA KECAMATAN LIANG ANGGANG KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Zulipah Mahdalena; Ahmad Baparki; Rohansyah (Chlorophyl, 2025)
One of the main obstacles in the marketing chain is the lack of efficiency at various stages. The aim of this research is to determine the marketing chain of the red ginger business, the amount of costs, revenues and income and to find out the problems faced by the red ginger juice business actors. Observations were carried out using the case study method. The results obtained are variable costs, namely variable costs Rp. 1,908,000.00. fixed costs Rp. 34,880.13, labor costs Rp. 600,000.00, marketing costs Rp. 75,000.00 total cost Rp. 1,942,880.13. receipt Rp. 3,000,000.00 and income of Rp. 1,092,000.00 The marketing chain consists of several distribution stages, namely Producer - Collector - Retailer - Final Consumer.